1958
DOI: 10.1038/1821230b0
|View full text |Cite
|
Sign up to set email alerts
|

A New Form of Tricalcium Phosphate

Abstract: may be increased by the suction induced by the rapidly flowing water at the tip.Mayne 1 has shown that rapid oxidation of ferrous hy~roxide at a_pH_value greater than 5 gives goethite while slow oxidation leads to the formation of an intermediate between magnetite and ferric oxide (yFe 20 3 ). Thus the formation of goethite in the present case is readily explained. The formation of magnetite, the second constituent, is not likely to occur in the same area at the same time as goethite since slow oxidation would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1968
1968
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…Since the highenergy barrier stabilizes the metastable a phase at room temperature, its lowering should result in rapid transition and presence of the low-temperature solid solution in samples quenched from high temperatures. At the same (8) time, the a 0 modification of Ca 3 (PO 4 ) 2 could be not obtained by quenching [4].…”
Section: Phase Equilibria Studymentioning
confidence: 93%
See 3 more Smart Citations
“…Since the highenergy barrier stabilizes the metastable a phase at room temperature, its lowering should result in rapid transition and presence of the low-temperature solid solution in samples quenched from high temperatures. At the same (8) time, the a 0 modification of Ca 3 (PO 4 ) 2 could be not obtained by quenching [4].…”
Section: Phase Equilibria Studymentioning
confidence: 93%
“…The phosphate was prepared in a solid state by the ceramic method according to method proposed in [42]. In this synthesis route, a stoichiometric mixture of CaCO 3 4 . The chemical composition of samples under study is shown in the Tab.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Ando1,2) identified the principal mineral of the phosphate to be a solid solution of a new compound "A" Ca 5Na2(PO4) 4, and suggested that the crystals of "A" might consist of a superlattice of hexagonal…”
mentioning
confidence: 99%